2022
DOI: 10.3390/v14020341
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Pathogenicity of a Novel Soybean-Infecting Monopartite Geminivirus in China

Abstract: Soybean is a major legume crop that plays an important role in food production, industrial production, and animal husbandry. Here, we characterize a novel soybean-infecting monopartite geminivirus identified in China. Analysis of the contigs de novo assembled from sequenced small interfering RNAs, followed by PCR, cloning, and sequencing, the complete viral genome was determined to be 2782 nucleotides. The genome contains the conserved nonanucleotide sequence, TAATATTAC and other sequence features typical of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Geminiviruses are among the most devastating plant pathogens worldwide (Roumagnac et al ., 2021). The documented geminiviruses that attack soybean include mung bean yellow mosaic virus (MYMV) (Malathi and John, 2008), soybean crinkle leaf virus (SCLV) (Iwaki et al ., 1983), soybean mild mottle virus (SbMMV) and soybean chlorotic blotch virus (SbCBV) (Alabi et al ., 2010), soybean blistering mosaic virus (SbBMV) (unpublished), and soybean yellow leaf curl virus (SbYLCV) (Du et al ., 2022); all of these viruses belong to the genus Begomovirus of the family Geminiviridae. However, phylogenetic analysis of the full‐length genome showed that SbSGSV is distinct from these documented geminiviruses as well as the 14 established genera of the Geminiviridae family.…”
Section: Discussionmentioning
confidence: 99%
“…Geminiviruses are among the most devastating plant pathogens worldwide (Roumagnac et al ., 2021). The documented geminiviruses that attack soybean include mung bean yellow mosaic virus (MYMV) (Malathi and John, 2008), soybean crinkle leaf virus (SCLV) (Iwaki et al ., 1983), soybean mild mottle virus (SbMMV) and soybean chlorotic blotch virus (SbCBV) (Alabi et al ., 2010), soybean blistering mosaic virus (SbBMV) (unpublished), and soybean yellow leaf curl virus (SbYLCV) (Du et al ., 2022); all of these viruses belong to the genus Begomovirus of the family Geminiviridae. However, phylogenetic analysis of the full‐length genome showed that SbSGSV is distinct from these documented geminiviruses as well as the 14 established genera of the Geminiviridae family.…”
Section: Discussionmentioning
confidence: 99%
“…to beans [34] and tobacco [35][36][37][38]. Since the SoSGV coat protein shares high homology with mastreviruses [29], and the coat protein determines the insect vector specificity…”
Section: Discussionmentioning
confidence: 99%
“…The common brown leafhopper can also transmit tobacco yellow dwarf virus ( Mastrevirus, Geminiviridae ) to beans [34] and tobacco [3538]. Since the SoSGV coat protein shares high homology with mastreviruses [29], and the coat protein determines the insect vector specificity [39], the phylogenetic relations of SoSGV coat protein may explain why leafhopper, other than whitefly [13], transmits SoSGV. Leafhoppers are shown to transmit plant geminiviruses in a persistent circulative manner [40], and the common brown leafhopper has a comparatively broad host plant range [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations